Can food safety shortfalls disrupt 'Ag for Nutrition' gains? Evidence from Eid al-Adha. (February 2019) - Schwab, Benjamin; Armah, Ralph
Highlights: Increasing smallholder livestock is seen as key to improving children's nutrition. Poor meat processing infrastructure increases food safety risks of such programs. We study a holiday in which large numbers of ruminants are slaughtered and consumed. Diarrhea rates of children in rural areas increase following this holiday. Results reinforce food safety concerns of Ag-for-Nutrition livestock interventions. Abstract: The international health community has stressed the need to raise consumption levels of animal-source foods in developing countries. Development programs based on so-called 'agriculture for nutrition' strategies emphasize the importance of smallholder livestock production to achieve these goals. While much of the literature has highlighted the high nutritional potential of such foods, little attention has been paid to infrastructural deficiencies for handling and processing animal-source foods, particularly meat. Such shortfalls in food safety have the potential to counteract some health gains, especially if renewed efforts to increase animal consumption are not combined with improved processing capacity. The spike in meat consumption among Muslims worldwide on Eid al-Adha provides a natural experiment to test the extent to which such food safety concerns are justified. Meat processing on this holiday often exceeds the capacity of formal slaughter and processing infrastructure, and thus provides an excellent opportunity to observe the implications of a rapid intensification of meat production and consumption across several countries. Using Demographic and Health Survey (DHS) data from countries in Africa and Asia, we estimate the impact of this holiday on the incidence of diarrheal illness among children. Eid al-Adha provides a plausibly exogenous source of variation in home or informally sourced meat consumption among Muslims, a natural comparison group (Non-Muslims) and independence from seasonal influences (the holiday follows the lunar Islamic calendar). We find that relative to non-Muslims, diarrhea morbidity increases for Muslim children following Eid al-Adha by 18 percent. No such similar increase is found on Eid al-Fitr, a similarly important Muslim holiday without extensive home slaughter. These findings reinforce the importance of food safety concerns in livestock sector interventions.